NON-GAUSSIANITY IN THE COSMOLOGICAL INFLATIONARY MODEL OF SINGLE SCALAR FIELD WITH SLOW-ROLL INFLATION, AND EINSTEIN-SCALAR-GAUSS-BONNET GRAVITY - Agung, Afiq
Non-Gaussian statistics in the distribution of Large-Scale Structures (LSS), and fluctuations in the Cosmic Microwave Background (CMB) temperature, can be used to constrain inflation models. Data on the cosmic microwave background from Planck (2015) are able to provide up-to-date limits on the parameters that control the level of non-Gaussianity in a given inflation model, thus favoring or disliking a particular model. Making the non-Gaussianity parameter investigated in this work can be a reference whether or not it is a good parameter in limiting the cosmological inflation model. Starting from random field statistics, this study examines the non-Gaussianity of the single scalar field cosmological inflation model (symbol) with slow-roll parameters. Then try to be tested further on the Einstein-scalar-Gauss-Bonnet 3+1 gravitational inflation model. The non-Gaussian signature generated by the model is quantified, and the parameters that control the level of non-Gaussianity are limited using data from Planck (2015). The results from the non-Gaussianity investigation in the Einstein-scalar-Gauss-Bonnet 3+1 inflation model can then be compared with a single scalar field model, slow-roll inflation. The method used in investigating non-Gaussianity in this study is the 'in-in' formalism, applied after obtaining the 3-point terms (symbol) (constant density curvature perturbation) from perturbation expansion to the third order. The 3-point correlation function helps in knowing the bispectrum that is used to investigate the non-gaussinity of the inflation model. The results of this study show that, (1) the two models tested are slow-roll models that are suppressed in the squeezed limit, because they have the dominant (formula) local; (2) the two models tested have the same nonGaussianity results because the Gauss-Bonnet term in the second model has a coupling function that is zero after being transformed to the ADM 3+1 formalism.